Senegal - The Urban Development and Decentralization Program - Farvacque-Vitkovic, C.; Godin, L. (World Bank, Washington, DC, 2012)
After twenty-five years of experience in the urban development sector in Africa and nearly 400 projects involving a combined investment of US$25 billion, an in-depth study distill lessons from this experience and identifies strategic thrusts for future operations. The future of African cities: urban development issues and priorities present policy guidelines already built into a number of new projects. This article deals initially with the African situation and then looks at the Senegal experience.